MATH ANXIETY IN ELEMENTARY SCHOOL STUDENTS: A PHENOMENOLOGICAL STUDY OF LEARNING EXPERIENCES IN THE CLASSROOM - Sutrisno, Agus Hari; Murtafiah, Wasilatul; Handhika, Jeffry; Maruti, Endang Sri (JURNAL EDUSCIENCE, 2026)
Purpose – This study phenomenologically examines the forms, sources, and dynamics of mathematics anxiety among students at SDN 1 Kedungrejo, Probolinggo Regency. At the elementary level, mathematics anxiety is critical, as it can hinder learning and slow students’ numeracy skill development.Methodology – The study uses a descriptive qualitative approach and a phenomenological case study design. Data came from classroom observations, interviews, and triangulation with the principal, mathematics teacher, and five students with varying anxiety levels. Analysis followed the Miles, Huberman, and Saldaña model: data reduction, narrative presentation, and drawing conclusions.Findings – The results show: (1) mathematics anxiety is an affective and socio-pedagogical construct shaped by classroom interactions and teaching patterns; (2) the anxiety stems not just from students' internal conditions, but also school structures, learning culture, and curriculum pressure; and (3) it arises from complex interplay among cognitive, emotional, and social factors in students’ daily learning.Contribution – These results show that mathematics anxiety in elementary students is multidimensional. It calls for a more humanistic, emotionally supportive approach to teaching to strengthen students' self-efficacy.